Colonic Stool Burden a Useful Surrogate for Slow Transit Constipation as Determined by a Radiopaque Transit Study. (March 2019) - Cangemi, David J.; Flanagan, Ryan; Barshop, Kenneth; Kuo, Braden; Staller, Kyle
Abstract : OBJECTIVES: Plain film abdominal x-ray (AXR) is frequently used in the evaluation of constipation, but studies assessing the association between stool burden on AXR and colonic transit have been limited. We sought to investigate the relationship between colonic stool burden and slow transit constipation, as determined by a radiopaque marker (ROM) transit study. METHODS: A retrospective cohort population was assembled, consisting of adult patients with chronic constipation who underwent testing with both a ROM study and anorectal manometry at 2 tertiary care centers over 5 years. Stool burden was graded by 2 independent observers, with colonic transit being assessed by the Hinton method. RESULTS: Of 361 patients, 145 (40.3%) had slow transit constipation, and women were more likely than men to have slow transit constipation (42.3% vs 26.5%, P = 0.04). The mean stool burden scores by observer 1 and observer 2 for patients with slow transit constipation were significantly higher than the mean stool burden scores for patients with normal transit constipation (8.1 ± 1.6 vs 6.9 ± 1.9, P < 0.0001; 8.5 ± 1.5 vs 5.8 ± 1.6, P < 0.0001). The Pearson correlation coefficient for the stool burden score and number of remaining ROMs was 0.31 (moderate) for observer 1 ( P < 0.0001) and 0.62 (strong) for observer 2 ( P < 0.0001), whereas the Pearson correlation coefficient for interrater reliability of the stool burden score was 0.58 ( P < 0.0001), indicating a strong correlation. The ideal score cutoff for both observers was 7, with moderate agreement by Cohen's kappa (0.43, P < 0.0001). CONCLUSIONS: Stool burden assessment on AXR may be a reliable alternative ROM study in the assessment of colonic transit.